Sustained Responses to Measles Revaccination at 24 Months in HIV-infected Children on Antiretroviral Therapy in Kenya. Issue 12 (December 2017) - Newman, Laura P.; Njoroge, Anne; Magaret, Amalia; Chohan, Bhavna H.; Gitomea, Veronicah W.; Wald, Anna; Gorstein, Jonathan; Overbaugh, Julie; Wamalwa, Dalton; Maleche-Obimbo, Elizabeth; Nduati, Ruth; Farquhar, Carey
Abstract : Background: There are limited data on whether HIV-infected children in resource-limited countries who are receiving antiretroviral therapy (ART) are able to produce sustained, protective levels of measles antibody after multiple measles vaccinations. Methods: We administered an additional measles vaccine to HIV-infected children 15 months to 12 years of age receiving ART in Nairobi, Kenya. Measles antibody concentrations were determined by enzyme-linked immunosorbent assay at enrollment, 1 month, 12 months and 24 months post revaccination. Results: At enrollment, 125 (54%) of 232 study participants had protective concentrations of measles antibody. Measles seropositivity increased to 98% of all children at 1 month post revaccination but decreased to 71% at 12 months and 60% at 24 months post revaccination. Measles seroconversion and sustained measles seropositivity among those who were measles seronegative at enrollment was 25% at 24 months post revaccination. In this group, 39% of children with <50 copies/mL plasma HIV RNA measles seroconverted compared to 4% of children with plasma HIV RNA ≥1000 copies/mL ( P = 0.018). Conclusions: Measles revaccination can result in a sustained antibody response in a subset of HIV-infected children receiving ART, especially among those with HIV suppression.